All Days 2006
DOI: 10.2118/100516-ms
|View full text |Cite
|
Sign up to set email alerts
|

Impact of In-Situ Sulfate Stripping on Scale Management in the Gyda Field

Abstract: While barium stripping is commonly observed in sandstone reservoirs where seawater mixes with formation water that may be rich in calcium, strontium and barium ions, this paper presents evidence for in situ sulphate stripping in a sandstone reservoir. The formation brine composition suggests that a moderate to severe barite scaling tendency will require inhibitor concentrations in the range of 10–50 ppm to control scale, but in practice concentrations < 5 ppm are adequate. Investigation of the produced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…1 shows that there is a progressive decline in [Ba] (barium concentration) at low IWF (0%~50%), then [Ba] can be observed to remain very low in the produced brine from 60% IWF and above. As a whole, this kind of Ba trend is similar to some typical barium behaviours which have been frequently observed in other seawater flooded North Sea sandstone reservoirs (Paulo et al, 2001;Mackay, E.J., 2006;Houston et al, 2006;Gomes et al, 2012). However, in the Miller field, the depletion in Ba at all seawater fractions is significantly lower than observed previous in other fields.…”
Section: Analysing and Modelling Of Geochemical Datasupporting
confidence: 87%
See 1 more Smart Citation
“…1 shows that there is a progressive decline in [Ba] (barium concentration) at low IWF (0%~50%), then [Ba] can be observed to remain very low in the produced brine from 60% IWF and above. As a whole, this kind of Ba trend is similar to some typical barium behaviours which have been frequently observed in other seawater flooded North Sea sandstone reservoirs (Paulo et al, 2001;Mackay, E.J., 2006;Houston et al, 2006;Gomes et al, 2012). However, in the Miller field, the depletion in Ba at all seawater fractions is significantly lower than observed previous in other fields.…”
Section: Analysing and Modelling Of Geochemical Datasupporting
confidence: 87%
“…However, the role of the reservoir was totally neglected in all of thermodynamic modelling work which is based on the fundamental assumption that the potential scale precipitation will be due to pure mixing of formation and injected water in the production well. However, it has been reported in some recent publications that both of brine mixing and geochemical reactions take place within the reservoir and the chemical composition of produced water would then be altered by them before arriving at producers (Paulo et al, 2001;McCartney et al, 2005;Houston et al, 2006;Mackay et al, 2006;Gomes et al, 2012;Fu et al, 2012). This paper reveals some fluid/fluid and fluid/rock interactions occurring in the reservoir through combining produced water chemical compositional data with geochemical and reservoir simulation model.…”
Section: Introductionmentioning
confidence: 83%
“…Therefore, reservoirs E, F, G and H, as well as the Gyda field 6,12 show strong evidence that sulphate reacts with calcium deep in the reservoir. It is important to observe that in all the cases the reservoir temperature is above 120ºC and the calcium concentrations in the formation water are higher than 7000 mg/l.…”
Section: Fig 18 -Comparison Between the Magnesium Concentration Expementioning
confidence: 92%
“…In this case sulphate stripping in situ was observed due to precipitation of calcium sulphate 6 . Indeed, the Gyda field is not an exception 13 and the work presented in the current paper has identified that in reservoirs with temperatures above 120ºC and rich in calcium (> 7000mg/l) the typical behaviour is for anhydrite precipitation deep in the reservoir.…”
Section: Introductionmentioning
confidence: 90%
“…Several studies have demonstrated that reactions occurring in the reservoir as a result of waterflood can result in modifications to the produced water compositions and scaling potential (Mackay et al, 2006;McCartney et al, 2010a;McCartney et al, 2007;e.g. Sorbie and Mackay, 2000).…”
Section: Potential Occurrence Of Reservoir Reactionsmentioning
confidence: 99%